Thyroidectomy in laryngectomy-rationale and extent - Shanmugam, Subbiah; Raja, Saktheeswaran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: To study the incidence of thyroid gland invasion by laryngeal carcinoma (LC) and the risk factors that may predispose to thyroid gland involvement, aiding the surgeons to develop an evidence-based plan for the management of the thyroid gland during total laryngectomy. Methods: A retrospective analysis of patients with carcinoma larynx treated at government Royapettah hospital, Chennai between January 1, 2013, and December 31, 2020, was done. The total number of final pathology reports retrieved from our hospital system for patients who met the inclusion criteria within the specified time frame was 43. Results: The thyroid gland was found to be invaded by LC in 13 patients (30.2%). Three patients (3/13) had only microscopic involvement while 9 patients showed gross extension. Four pathological features were found to have Statistically significant association with the incidence of thyroid gland invasion by laryngeal carcinoma. Patients with primary tumor pathological stage T4a were 30/43, with 11 patients showing thyroid gland invasion. 20 patients had subglottic invasion by the LC, with 10 patients showing thyroid gland invasion. Poorly differentiated carcinoma incidence was 13, with 9 patients showing thyroid gland infiltration. Conclusions: Several risk factors are associated with higher incidence of invasion of the thyroid gland by laryngeal carcinoma. Identification of these factors can help surgeons develop a surgical strategy for the management of the thyroid gland during total laryngectomy.